High pressure and thermal pasteurization effects on sweet cherry juice microbiological stability and physicochemical properties - Queirós, R.P. (2022)
This study evaluated high pressure processing (P1 – 400 MPa/5 min; P2 – 550 MPa/2 min) and thermal pasteurization (TP – 70°C/30 s) effects on sweet cherry juice’s microbiological and physicochemical parameters, during four weeks of refrigerated storage. All treatments reduced the microbiological load to undetectable levels not affecting total soluble solids and titratable acidity. The pH increased with all treatments, however, it decreased during storage. Phenols were differently affected: TP increased them by 6%, P1 had no effect while P2 decreased them by 11%. During storage, phenols in control and TP samples decreased by 26% and 20%, P1 samples decreased them by 11% whereas P2 showed no variation. TP had no effect on anthocyanins, while pressure treatments increased them by 8%. Anthocyanins decreased during storage, particularly in the control and P1 (decreasing 41%). All treatments had no effect on antioxidant activity until the 14th day, thereafter high pressure processing samples showed the highest antioxidant activity.